RANCANG BANGUN SISTEM INFORMASI PENJUALAN BERBASIS WRB PADA STUDI KASUS RAJAWALI PETSHOP KOTA BATAM - Monalisa, Monalisa; Saragih, Saut (Computer Science and Industrial Engineering, 2022)
Rajawali Petshop, which is one of the stores that provide products for pets, which has been operating since January 2020, has continued to grow until now. Currently the sales system used by Rajawali Petshop is still using the conventional system, where consumers have to go to Rajawali Petshop to choose and buy the desired product, sometimes employees have to ask the warehouse first to see the availability of the product stock they are looking for, thus making consumers have to wait. After the product sought by the consumer is obtained, the consumer makes a payment to the place provided, namely the cashier. The cashier will recapitulate the sales data by transferring the proof of payment into the notebook to be used as a report to the Petshop owner. The method applied in this research activity applies the Waterfall model SDLC method. The waterfall method is very structured and easy to understand, because it is like a waterfall that descends down in stages. From the results of the analysis, design and manufacture of application programs that have been described, it can be concluded that web information systems can help consumers buy products online, this is considered to provide convenience for consumers, especially shop owners in disemenathing imformation and consumers in accessing the information need through the menus in the information system.